PENGETAHUAN MASYARAKAT TENTANG BEYOND USE DATE (BUD) PADA PENGGUNAAN OBAT TETES MATA - Rossetyowati, Diyan Ajeng; Nurmalasari, Dewi Riskha; Rohma, Tamara Aisa (Ensiklopedia Research and Community Service Review, 2024)
Eye drops are sterile preparations in the form of solutions or suspensions used by dripping on the mucous membranes and eyelids. Eye drops should not used more than one month after the lid is opened.  Beyond Use Date (BUD) is the time limit for the use of a medicinal product after it has been compounded or prepared or after its primary packaging has been opened or tampered with. This study aimed to determine the description of public knowledge about Beyond Use Date (BUD) in eye drops. This is a descriptive quantitative study. Sample collected by non probability with consecutive sampling method. There are 66 respondents from Gebang Poreng, Jember, who had met the inclusion criteria. Data was obtained by distributing questionnaires filled out by the respondents. Based on the results of the study it can be concluded the respondent's knowledge is included in fewer categories with a percentage is 54,88%.Keywords: Eye drops, Beyond Use Date